TET enzymes and DNA hydroxymethylation in neural development and function : how critical are they? - Pereira, Mafalda Santiago (2014)
Epigenetic modifications of the genome play important roles in controlling gene transcription thus regulating several molecular and cellular processes. A novel epigenetic modification - 5-hydroxymethylcytosine (5hmC) - has been recently described and attracted a lot of attention due to its possible involvement in the active DNA demethylation mechanism. TET enzymes are dioxygenases capable of oxidizing the methyl group of 5-methylcytosines (5mC) and thus converting 5mC into 5hmC. Although most of the work on TET enzymes and 5hmC has been carried out in embryonic stem (ES) cells, the highest levels of 5hmC occur in the brain and in neurons, pointing to a role for this epigenetic modification in the control of neuronal differentiation, neural plasticity and brain functions. Here we review the most recent advances on the role of TET enzymes and DNA hydroxymethylation in neuronal differentiation and function.